(untitled) (Acta Scientiarum. Biological Sciences, 2016)
The effects of different light quality treatments on in vitro growth and multiplication of sugarcane (RB867515) were investigated. The plantlets were cultivated on MS medium containing 1.3 Î¼M 6-benzylaminopurine (BAP), and exposed to five light treatments: three combinations of blue/red LED (70:30, 50:50, 30:70), white-LED and fluorescent lamps, during 24 days. Among the LED light treatments, blue/red combination in 50:50 proportions proved to have the best results for stem length, fresh mass, leaf number and shoot multiplication. Higher content of photosynthetic pigments was also obtained with LEDs. Results suggested that the light quality emitted by LEDs was suitable for plant growth and development and it may be used as alternative and economic light source for micropropagation of sugarcane variety under analysis.